CORRECTION OF MORPHOFUNCTIONAL DISORDERS IN EXPERIMENTAL PREECLAMPSY BY COMBINED USE OF TRIMETAZIDINE AND PURIFIED MICRONIZED FLAVONOID FRACTION AS WELL AS THEIR COMBINATIONS WITH METHYLAMPSY - O. E. Antsiferova; M. P. Teleshchenko; Yu. M. Tsuverkalova; M. V. Pokrovsky; V. V. Gureev; M. A. Zatolokina; A. V. Gureeva (Фармация и фармакология (Пятигорск), 2021)
The aim of the experiment was to determine the effectiveness of the combined use of trimetazidine and a purified micronized flavonoid fraction, as well as their combinations with methyldopa, in comparison with monotherapy with the same drugs in the correction of morphofunctional disorders arising in the conditions of experimental preeclampsia. An integrated/multimethodology approach is the most effective way of treatment for preeclampsia. Therefore, an urgent task of modern pharmacology is to study the effectiveness of new drugs when used in combinations, as well as the drugs included in the standards for treatment.Materials and methods. The study was carried out at the Research Institute of Pharmacology of Living Systems of Belgorod State National Research University. The experiment was performed on 200 female Wistar rats, weighing 250–300 g, in which an ADMA-like model of preeclampsia had been reproduced. To assess the degree of correction of emerging morphological and functional disorders, the following parameters were involved: blood pressure, a coefficient of endothelial dysfunction, microcirculation in the placenta, proteinuria, fluid contents in the greater omentum, morphometric indicators of placental tissues and fetal height and weight parameters.Results. The combined use of trimetazidine (Preductal® MB) 6 mg/kg and a purified micronized flavonoid fraction (Detralex®) 260 mg/kg, as well as their combination with methyldopa (Dopegit®) 86 mg/kg, leads to a more pronounced decrease in the blood pressure, compared with a decrease in the coefficient of endothelial dysfunction by 2.22, 2.19 and 1.94 times, respectively, in relation to “untreated” animals. There was an increase in microcirculation indices in the placenta by 2.35, 2.21 and 2.03 times, respectively. In addition, there was an improvement in morphological parameters in the placenta and fetuses.Conclusion. The results of the study showed a greater effectiveness of the combined use of the studied drugs in experimental preeclampsia compared to their monotherapy. This indicates the prospects for the use of trimetazidine and purified micronized flavonoid fraction in the complex therapy for preeclampsia and the need for further research in this direction.